Mathematical Modeling: A Bridge to STEM Education - KERTİL, MAHMUT (NECMETTIN ERBAKAN UNIV, 2016)
The purpose of this study is making a theoretical discussion on the relationship between mathematical modeling and integrated STEM education. First of all, STEM education perspective and the construct of mathematical modeling in mathematics education is introduced. A review of literature is provided on how mathematical modeling literature may contribute to theoretical conceptualization of STEM education by specifically addressing the professional competencies that teachers need. The discussion followed on how mathematical modeling activities and project-based learning contexts contribute to integrated STEM education by providing two research-based experiences, one of which is the model rocketry project carried out by pre-service physics teachers and the other one of which is a mathematical modeling activity solved by pre-service mathematics teachers.
Keywords: STEM education; Mathematical modeling; Project-based learning; Model-eliciting activities; TEACHERS